Exploring the role of planned and unplanned biodiversity in the soil health of agroecosystems - Kelly, Courtland, author; Fonte, Steven J., advisor; Schipanski, Meagan E., committee member; Wallenstein, Matthew, committee member; Hall, Ed, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: cover crops; soil macrofauna; rhizosphere microbiome; agroecology